The generalized polynomial Moon–Rand system. (February 2018) - Giné, Jaume; Valls, Claudia
Abstract: The Moon–Rand systems, developed to model control flexible space structures, are systems of differential equations in R 3 of the form u ̇ = v, v ̇ = − u − u w, w ̇ = − λ w + f ( u, v ) . We give a partially positive answer to a recently conjecture for a special class of such systems, called the generalized polynomial Moon–Rand systems in the case when λ ∈ ( 0, ∞ ) and f is either a homogeneous cubic, quartic, quintic or sextic polynomial.